Isolation, purification, and structural characterization of biosurfactants derived from indigenous probiotics Lactobacillus helveticus MTCC5463 and Lactobacillus rhamnosus MTCC5462 - Pandey, Kamini; Kumari, Madhu; Mehtab, Sameena; Singhal, Barkha (Frontiers in Bacteriology, 2026)
The present study investigates the extraction and characterization of biosurfactants from two Indian originated Lactobacillus probiotics. Biosurfactants derived through Lactobacillus species have potential applications in food, pharmaceutical, and biomedical sectors. In the current study, Lactobacillus helveticus MTCC5463 and Lactobacillus rhamnosus MTCC5462 species were aimed to extract, purify, and characterize surface-active properties of produced biosurfactants. The species were cultured in their selective medium and biosurfactants derived are extracted and purified through acid precipitation and solvent extraction. The characterization was performed through measurement of surface tension reduction emulsification index (E24), Fourier transform infrared spectroscopy (FTIR), gas chromatography–mass spectrometry (GC-MS), and 1H and 13C nuclear magnetic resonance (NMR) spectroscopy. The biosurfactants reduced surface tension from 72 mN/m (distilled water baseline) to 38.73 (± 0.05) mN/m and 41.30 (± 0.04) mN/m for L. helveticus MTCC5463 and L. rhamnosus MTCC5462, respectively. The emulsification activity was high (E24 > 70%) for various hydrophobic substrates such as petrol, diesel, mustard, and refined oil. FTIR and GC-MS revealed a glycolipid nature, with major fatty acid components such as butanoic acid. The 1H NMR data support an amphiphilic glycolipid structure characterized by long aliphatic fatty acid chains [δ 0.90–1.50 parts per million (ppm)] and esterified (or hydroxyl‐adjacent) methylene groups. The 13C NMR data are consistent with a biosurfactant structure comprising long aliphatic chains (δ 14.11; 29.35–31.92 ppm), methylene carbons adjacent to ester or hydroxyl groups (δ 40.95 ppm), and oxygenated carbons (δ 76.70–77.34 ppm) indicative of glycerol or sugar headgroup backbone. These findings highlighted that Lactobacillus-derived biosurfactants have strong surface-active properties that can be explored for various biomedical applications in future studies.